Assessing molecular changes underlying isopropylated phenyl phosphate (IPP)-induced larval sensorimotor response deficits in zebrafish - Sunil Sharma; Alfredo Rojas; Abhishek Gour; Rosemaria Serradimigni; Connor Leong; Abhisheak Sharma; Subham Dasgupta (Ecotoxicology and Environmental Safety)
Isopropylated phenyl phosphates (IPP) are an additive organophosphate flame retardant (OPFR) that has been extensively used in furniture, electronics, automobiles, plastics, and children’s products to slow down the spread of fire but its continued leaching leads to toxicity concerns. Toxicological information on this important legacy contaminant is limiting. Using zebrafish, our prior whole embryonic RNA-seq data revealed disruption of gene sets enriched for DNA methylation, neurotransmitter synthesis, retinoic acid signaling and eye development. Within this study, we used zebrafish embryos to systemically study these biological targets. Our initial range-finding experiments revealed significant morphological impacts like pericardial edema, yolk sac edema and spinal curvature, coupled with a significant increase in the levels of dopamine and 3-methoxytyramine. We then conducted an in vitro retinoic acid receptor (RAR) assay and showed that IPP inhibits RARα, but not RARβ and RARγ. Following this, our larval behavioral (photomotor and acoustic response assays) at environmentally relevant, sub-μM concentrations showed significant hypoactivity, indicating sensorimotor deficits within exposed embryo. We then assessed global DNA methylation using a combination of whole-mount immunohistochemistry and ELISA for 5-methylcytosine (5-mC) and showed significant IPP-induced hypermethylation within whole embryo in situ. Finally, we focused on eye and brains as targets. We dissected eyes and brains from IPP-exposed larvae and conducted 5-mC assessments and mRNA-sequencing. Interestingly, neither of the organs showed differences in 5-mC levels and the brains also did not show substantial transcriptomic effects. However, for eyes, mRNA sequencing showed 135 differentially expressed genes and these were enriched for several nervous system-associated pathways, including voltage gated ion channel activity, synaptic transmission and neurotransmitter signaling. Collectively, our data shows that IPP exposures can disrupt a battery of biological pathways spanning neurometabolomic, genetic, epigenetic as well as organ-level targets. Notably, these impacts occur at concentrations within environmental relevance where overt toxic morphological phenotypes are not recorded. Future work will focus on understanding the contribution of these molecular targets to behavioral phenotypes.